Coccolithophore abundance, biomass and particulate inorganic carbon concentration in the South China Sea in June/July 2018 - Xiaobo Jin; Chuanlian Liu; Juan Xu; Xianghui Guo (PANGAEA, 2022)
We investigated coccolithophore abundance, coccolith calcite biomass, and particulate inorganic carbon (PIC) concentration in the deep chlorophyll maximums in the South China Sea. The field investigation was conducted on board the research vessel “TAN KAH KEE (JiaGeng)” during cruise NORC2018-05 from June to July, 2018. 2L of water samples were collected with a conductivity-temperature-depth (CTD) rosette sampler and filtered on 0.8 μm pore-size polycarbonate membranes. Coccolithophores were checked using a light microscope. Coccolith calcite biomass was calculated based on coccolithophore abundance and average coccolith mass. 3L of water samples for PIC were also collected and filtered on 0.8 μm pore-size polycarbonate membranes. PIC was determined by measuring the [Ca2+] concentration in seawater using inductively coupled plasma–mass spectrometry.